A high thermal conductivity gel powder and its preparation method and application
By preparing graphene hydrogels in polymers and combining aminolated boron nitride nanosheets, a three-dimensional thermal conductivity network is formed, which solves the problem of improving thermal conductivity of polymer thermal conductivity under high load conditions, and achieves high frequency and high power Effective heat dissipation of electronic devices.
Patent Information
- Application Number
- CN202411330706.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-24
AI Technical Summary
The existing polymer thermal conductivity has limited improvement in thermal conductivity under high load conditions and its structure is unstable, making it difficult to meet the heat dissipation needs of high-frequency and high-power electronic devices.
Graphene oxide and polyethylene glycol are used as raw materials to prepare graphene hydrogels, combine amino acid boron nitride nanosheets, and mix graphene and amino acid boron nitride nanosheets through polyamic acid medium to form three-dimensional Thermal conduction network improves the thermal conductivity of composite materials.
It significantly improves the thermal conductivity and mechanical strength of composite materials, ensures structural stability and thermal conductivity in 3D printing and melting reprocessing, and meets the heat dissipation needs of high-frequency and high-power electronic equipment.
Smart Images

Figure CN118834413B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of honeycomb materials, and in particular relates to a high thermal conductivity gel powder and a preparation method and application thereof. Background Art
[0002] Miniaturized, highly integrated, functionalized, and high-power electronic devices are gradually emerging and applied to all aspects of life; at the same time, the requirements for the comfort and smoothness of electronic products are becoming higher and higher. With the increase in the frequency and power of semiconductor chips and the tight packaging of integrated circuits, a large amount of heat will be generated during the operation of the equipment. In order not to affect the operating efficiency of the equipment, it is necessary to dissipate heat in time, otherwise it will accumulate and form many hot spots. At very high temperatures, these local hot spots have a significant impact on the performance and service life of microelectronic devices. Therefore, an effective thermal management system is crucial to reducing the temperature of local hot spots in high-power electronic devices, which puts forward new requirements and challenges for traditional thermal conductive materials.
[0003] Polymers have the advantages of strong processability, low density, and adaptability to multiple environments, so they have received great attention in the fields of electronics, engineering, energy, aerospace, etc. However, since the thermal conductivity of polymers themselves is poor and most of them are thermal insulation materials, it is difficult to meet the heat dissipation requirements of most electronic products. Therefore, it is necessary to improve the thermal conductivity of polymer materials through appropriate means and develop high thermal conductivity, stable performance, and safe thermal conductive polymer thermal interface materials to meet the growing demand for heat dissipation performance.
[0004] Due to the high disorder of polymer chains, the phonon scattering phenomenon is very obvious in polymers. The scattering of phonons mainly occurs through collisions between phonons and interfaces between impurities and lattice defects, which makes its intrinsic thermal conductivity low. In practical applications, it basically cannot meet the requirements of heat dissipation, so it is necessary to develop thermally conductive polymer materials with excellent comprehensive performance. According to the differences in the preparation methods of thermally conductive composite materials, they can be roughly divided into two categories. One is a polymer that relies on its own performance without adding any other substances, that is, an intrinsic thermal conductive material; the other is a composite preparation of different forms of thermal conductive materials and polymers, which is called a filled thermal conductive material. The latter can be divided into a filler blended filling type and a prefabricated three-dimensional skeleton filling type according to the different composite forms of thermal conductive materials and polymers.
[0005] However, due to the huge interfacial thermal resistance at the filler-filler and filler-matrix interfaces, the thermal conductivity of composite materials prepared with thermally conductive fillers under high load does not show a significant improvement as expected. In addition, poor particle dispersibility and high loading levels of dispersed fillers severely reduce the performance of polymers. These factors prevent thermally conductive fillers from fully realizing their potential to enhance polymer thermal conductivity. Compared with the use of dispersed filler particles, the pre-constructed three-dimensional thermally conductive skeleton structure is an excellent way to create high-performance polymer-based thermally conductive materials because it ensures good filler distribution and forms a continuous thermally conductive network in the polymer matrix, interconnecting the touching fillers, increasing the density of the filler percolation network, providing a multi-channel phonon propagation path, and effectively reducing the interfacial thermal resistance that blocks phonon propagation, reducing the impact of interfacial thermal resistance on the improvement of thermal conductivity performance to a lower level. Using such a framework, the maximum degree of thermal conductivity of polymer thermally conductive materials can be obtained with a minimum amount of high thermally conductive filler filling. For example, three-dimensional interconnected structures of boron nitride and graphene foams have been widely used. However, the polymer melt is weakly dispersed, and the three-dimensional thermally conductive filler prepared by the prior art has poor interaction with the polymer matrix, resulting in large interface thermal resistance and low efficiency in forming thermal conductive channels, leading to low thermal conductivity. Summary of the invention
[0006] In view of the above-mentioned prior art, the object of the present invention is to provide a high thermal conductivity gel powder and a preparation method and application thereof.
[0007] To achieve the above object, the present invention adopts the following technical solution:
[0008] A method for preparing a high thermal conductive gel powder comprises the following steps:
[0009] (1) dispersing graphene oxide, a reducing agent, and polyethylene glycol in deionized water to obtain a graphene oxide mixed solution, sealing the mixed solution, and placing the mixed solution in an oven for heating to obtain a graphene hydrogel solution;
[0010] (2) dispersing polyamic acid powder in deionized water, adding an organic base, and stirring until the polyamic acid powder is completely dissolved to obtain a polyamic acid salt solution; the mass ratio of graphene oxide to polyamic acid powder is 1:(0.3-1); the mass ratio of polyamic acid powder to organic base is 1:(0.01-0.2);
[0011] Adding a small amount of organic base is intended to effectively control the salt degree of polyamic acid by limiting the degree of reaction between polyamic acid and organic base, so that a part of carboxyl groups can undergo grafting reaction with amino groups on the surface of aminated boron nitride nanosheets, so that polyamic acid can play the role of dispersant and connector, and improve the adhesion and dispersion degree of aminated boron nitride nanosheets;
[0012] (3) adding the aminated boron nitride nanosheets into the polyamic acid salt solution and dispersing by ultrasonication to obtain a polyamic acid salt mixed solution; the mass ratio of the polyamic acid powder to the aminated boron nitride nanosheets is 1:(0.1-1);
[0013] (4) adding the polyamic acid salt mixed solution dropwise to the graphene hydrogel solution while stirring, and allowing the solution to stand after the addition is complete to obtain a polyamic acid / boron nitride / graphene mixed hydrogel;
[0014] (5) The polyamic acid / boron nitride / graphene mixed hydrogel is freeze-dried, thermally imidized, and crushed to obtain a high thermal conductive gel powder.
[0015] There are many preparation technologies for polyimide / graphene gel materials in the prior art. However, they generally adopt the in-situ gel formation method (CN106750290A, CN110357067A, etc.), the graphene aerogel impregnation method (CN112094426A), and the polyamide acid hydrogel loaded graphene method (CN116218018A). The above-mentioned processes either prepare polyamide acid gel or graphene aerogel first, or prepare aerogel after blending polyamide acid with graphene, and the matrix structure is a polymer, which is structurally unstable and has poor mechanical properties. When used for 3D printing melt reprocessing, structural damage will occur. In order to overcome this problem, the inventors used polyethylene glycol and graphene oxide as raw materials to first prepare graphene hydrogel in previous work to construct a graphene-based gel material. As a good modifier, polyethylene glycol is not only conducive to the dispersion of graphene, but also can form hydrogen bonds with oxygen-containing functional groups such as carboxyl or hydroxyl groups on the surface of graphene, thereby enhancing the interaction between graphene sheets and improving the stability of the graphene hydrogel structure. The number average molecular weight of polyethylene glycol can be 400-5000, and can be specifically PEG400, PEG600, PEG800, PEG1000, PEG2000, PEG5000, etc.
[0016] The polyimide / graphene gel material prepared by the above method can effectively improve the mechanical properties of the composite material. However, since the matrix aerogel is prepared from graphene oxide as a raw material, there are a large number of wrinkles and defects on the graphene surface, resulting in a decrease in the thermal conductivity of the gel network. In particular, when it is used as a thermally conductive filler for thermoplastic polyurethane, a large amount of polyurethane material is filled in the internal voids of the gel, and the thermal conductivity of the gel skeleton will determine the thermal conductivity of the composite material as a whole. In order to make up for the defects of the graphene skeleton, the present invention introduces a certain amount of amino-modified boron nitride nanosheets. Boron nitride has extremely high thermal conductivity and mechanical strength, which can greatly improve the thermal conductivity and mechanical strength of the composite material. However, the chemical inertness of the surface of boron nitride makes it difficult to evenly disperse them in the polymer matrix, especially in the case of high filling amount, which will result in the inability to form a three-dimensional thermal conductive network based on boron nitride. The preparation of hexagonal boron nitride nanosheets by liquid phase ball milling belongs to the conventional process in the art (for example, CN 112409791 A, CN 112552681 A, etc.). The ball mill provides a gentle shear force and can produce high-quality hexagonal boron nitride nanosheets. Urea is used as a ball milling aid in the ball mill. Under the action of high-energy ball milling, it can form a new structure with boron nitride, making it easier for urea to combine with boron nitride and stabilize boron nitride after peeling, thereby obtaining a hexagonal boron nitride nanosheet material with a lateral size of hundreds of nanometers and a thickness of only a few nanometers. Furthermore, the surface active groups of the amino boron nitride nanosheets can undergo a grafting reaction with the residual carboxyl groups on the polyamic acid salt, effectively improving the adhesion efficiency of the amino boron nitride nanosheets and preventing the boron nitride nanosheets from falling off from the gel network during 3D printing melt reprocessing, affecting the formation of thermal conductivity pathways. Among them, when the mass ratio of polyamic acid powder to amino boron nitride nanosheets is 1:0.3-0.6, it is beneficial to exert the high thermal conductivity and high mechanical strength properties of the amino boron nitride nanosheets, and can prevent the amino boron nitride nanosheets from excessively blocking the gel pores and affecting the infiltration of thermoplastic polyurethane.
[0017] Furthermore, the preparation process of the polyamic acid powder in the present invention is as follows: using diamine monomer and dianhydride monomer as raw materials to disperse in an organic solvent for polycondensation reaction to prepare a polyamic acid solution; pouring the polyamic acid solution into deionized water for precipitation to obtain polyamic acid powder; the dianhydride monomer is at least one of 4,4'-biphenyl ether dianhydride, biphenyl tetracarboxylic dianhydride, 1,2,4,5-pyromellitic dianhydride, 3,3',4,4'-benzophenone tetracarboxylic dianhydride, bisphenol A type diether dianhydride, 4,4-oxydiphthalic anhydride, 1,2,4,5-cyclohexane tetracarboxylic dianhydride; the diamine monomer is at least one of p-phenylenediamine, m-phenylenediamine, diaminodiphenyl sulfone, 4,4'-diaminodiphenyl ether, 4,4'-diaminodiphenylmethane. The organic solvent is at least one of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide and N-methylpyrrolidone.
[0018] Step (1) The concentration of graphene oxide in the graphene oxide mixed solution is 0.5-2 mg / mL; the reducing agent is ascorbic acid, and the mass ratio of graphene oxide to the reducing agent is 1:(0.1-0.5); the mass ratio of graphene oxide to polyethylene glycol is 1:(0.01-0.1); the heating reaction temperature is 60-90°C and the time is 1-4h.
[0019] Furthermore, the organic base in step (2) is at least one of triethylamine, tripropylamine and triethanolamine.
[0020] Furthermore, the preparation process of the amino boron nitride nanosheets in step (3) is as follows: the hexagonal boron nitride powder, urea and deionized water are uniformly mixed and then put into a ball mill, and under the protection of inert gas, the amino boron nitride nanosheets are obtained by high-speed ball milling, washing and drying.
[0021] Furthermore, the mass ratio of hexagonal boron nitride powder to urea is 1:(15-30).
[0022] Furthermore, the ball mill speed is 400-500 rpm, the ball milling time is 5-10 h, and the inert gas is nitrogen.
[0023] Furthermore, washing is performed with deionized water for 3-5 times.
[0024] The present invention also provides an application of a high thermal conductivity gel powder, wherein the high thermal conductivity gel powder is used in the field of 3D printing polyurethane materials, and the polyurethane material comprises the following components in parts by weight:
[0025] 100 parts of thermoplastic polyurethane elastomer; 5-25 parts of high thermal conductivity gel powder; 1-5 parts of flow modifier.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] (1) First, graphene hydrogel is prepared to construct a graphene-based gel material. Polyethylene glycol, as a good modifier, is not only conducive to the dispersion of graphene, but also can form hydrogen bonds with oxygen-containing functional groups such as carboxyl or hydroxyl groups on the surface of graphene, thereby enhancing the interaction between graphene sheets and improving the stability of the graphene hydrogel structure.
[0028] (2) The graphene hydrogel impregnation process of polyamic acid salt / amino-boron nitride nanosheets not only further improves the mechanical properties of the gel material, but also improves the compatibility of graphene with thermoplastic materials such as polyurethane, which is conducive to meeting the process of secondary processing of 3D printing.
[0029] (3) Using polyamic acid salt as a medium to connect graphene gel and amino boron nitride nanosheets, graphene and amino boron nitride nanosheets can be mixed at the micron level. This micron-level dispersion can improve the dispersion of fillers in the thermoplastic polyurethane resin matrix, thereby forming more thermal conductivity pathways. The three-dimensional graphene gel is used as a reinforcing skeleton and thermal conductive filler, and the two-dimensional boron nitride nanosheets are used as thermal conductive reinforcing fillers. When used in combination with the three-dimensional graphene gel, a synergistic effect can be achieved to form a three-dimensional network thermal conductive pathway, thereby improving the thermal conductivity of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a scanning electron microscope image of the high thermal conductivity gel powder prepared in Example 5;
[0031] Figure 2 This is a scanning electron microscope image of the high thermal conductivity gel powder prepared in Comparative Example 1. DETAILED DESCRIPTION
[0032] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.
[0033] In order to enable those skilled in the art to more clearly understand the technical solution of the present application, the technical solution of the present application will be described in detail below in conjunction with specific embodiments.
[0034] The test materials used in the examples of the present invention are all conventional test materials in the art and can be purchased through commercial channels.
[0035] The preparation process of the amino boron nitride nanosheets in the following embodiments and comparative examples is as follows: hexagonal boron nitride powder, urea and deionized water are uniformly mixed and put into a ball mill, and under the protection of inert gas, high-speed ball milling, deionized water washing 5 times and drying are performed to obtain amino boron nitride nanosheets; wherein the mass ratio of hexagonal boron nitride powder to urea is 1:20; the ball mill speed is 400 rpm, and the ball milling time is 7 hours; the inert gas is nitrogen.
[0036] Example 1
[0037] A method for preparing a high thermal conductive gel powder comprises the following steps:
[0038] (1) Graphene oxide, a reducing agent and polyethylene glycol are dispersed in deionized water to obtain a graphene oxide mixed solution, which is then sealed and placed in an oven for heating to obtain a graphene hydrogel solution; the graphene oxide concentration in the graphene oxide mixed solution is 1 mg / mL; the reducing agent is ascorbic acid, and the mass ratio of graphene oxide to the reducing agent is 1:0.2; the mass ratio of graphene oxide to polyethylene glycol is 1:0.03; the heating reaction temperature is 65°C, and the time is 2 hours; the number average molecular weight of polyethylene glycol is 800;
[0039] (2) Dispersing polyamic acid powder in deionized water, adding an organic base, and stirring until the polyamic acid powder is completely dissolved to obtain a polyamic acid salt solution; the mass ratio of graphene oxide to polyamic acid powder is 1:0.3; the mass ratio of polyamic acid powder to organic base is 1:0.01; the organic base is triethylamine; the preparation process of polyamic acid powder is: using diamine monomer and dianhydride monomer as raw materials to disperse in N,N-dimethylformamide for polycondensation reaction to prepare polyamic acid solution; pouring the polyamic acid solution into deionized water for precipitation to obtain polyamic acid powder; the dianhydride monomer is bisphenol A diether dianhydride; the diamine monomer is 4,4'-diaminodiphenylmethane; the molar ratio of dianhydride monomer to diamine monomer is 1:1.02;
[0040] (3) adding the aminated boron nitride nanosheets into the polyamic acid salt solution and dispersing by ultrasonication to obtain a polyamic acid salt mixed solution; the mass ratio of the polyamic acid powder to the aminated boron nitride nanosheets is 1:0.3;
[0041] (4) adding the polyamic acid salt mixed solution dropwise to the graphene hydrogel solution while stirring, and allowing the solution to stand after the addition is complete to obtain a polyamic acid / boron nitride / graphene mixed hydrogel;
[0042] (5) The polyamic acid / boron nitride / graphene mixed hydrogel is freeze-dried, thermally imidized, and crushed to obtain a high thermal conductive gel powder.
[0043] A 3D printing polyurethane material comprises the following components in parts by weight:
[0044] 100 parts of thermoplastic polyurethane elastomer; 15 parts of high thermal conductivity gel powder; 3 parts of zinc stearate.
[0045] Example 2
[0046] A method for preparing a high thermal conductive gel powder comprises the following steps:
[0047] (1) Graphene oxide, a reducing agent and polyethylene glycol are dispersed in deionized water to obtain a graphene oxide mixed solution, which is then sealed and placed in an oven for heating to obtain a graphene hydrogel solution; the graphene oxide concentration in the graphene oxide mixed solution is 1 mg / mL; the reducing agent is ascorbic acid, and the mass ratio of graphene oxide to the reducing agent is 1:0.4; the mass ratio of graphene oxide to polyethylene glycol is 1:0.09; the heating reaction temperature is 85°C, and the time is 2 hours; the number average molecular weight of polyethylene glycol is 800;
[0048] (2) Dispersing polyamic acid powder in deionized water, adding an organic base, and stirring until the polyamic acid powder is completely dissolved to obtain a polyamic acid salt solution; the mass ratio of graphene oxide to polyamic acid powder is 1:0.8; the mass ratio of polyamic acid powder to organic base is 1:0.2; the organic base is triethanolamine; the preparation process of polyamic acid powder is: using diamine monomer and dianhydride monomer as raw materials to disperse in N,N-dimethylformamide for polycondensation reaction to prepare polyamic acid solution; pouring the polyamic acid solution into deionized water for precipitation to obtain polyamic acid powder; the dianhydride monomer is 4,4'-biphenyl ether dianhydride; the diamine monomer is 4,4'-diaminodiphenylmethane; the molar ratio of dianhydride monomer to diamine monomer is 1:1.02;
[0049] (3) adding the aminated boron nitride nanosheets into the polyamic acid salt solution and dispersing by ultrasonication to obtain a polyamic acid salt mixed solution; the mass ratio of the polyamic acid powder to the aminated boron nitride nanosheets is 1:0.6;
[0050] (4) adding the polyamic acid salt mixed solution dropwise to the graphene hydrogel solution while stirring, and allowing the solution to stand after the addition is complete to obtain a polyamic acid / boron nitride / graphene mixed hydrogel;
[0051] (5) The polyamic acid / boron nitride / graphene mixed hydrogel is freeze-dried, thermally imidized, and crushed to obtain a high thermal conductive gel powder.
[0052] A 3D printing polyurethane material comprises the following components in parts by weight:
[0053] 100 parts of thermoplastic polyurethane elastomer; 15 parts of high thermal conductivity gel powder; 2 parts of zinc stearate.
[0054] Example 3
[0055] A method for preparing a high thermal conductive gel powder comprises the following steps:
[0056] (1) Graphene oxide, a reducing agent and polyethylene glycol are dispersed in deionized water to obtain a graphene oxide mixed solution, which is then sealed and placed in an oven for heating to obtain a graphene hydrogel solution; the graphene oxide concentration in the graphene oxide mixed solution is 1 mg / mL; the reducing agent is ascorbic acid, and the mass ratio of graphene oxide to the reducing agent is 1:0.1; the mass ratio of graphene oxide to polyethylene glycol is 1:0.1; the heating reaction temperature is 90°C, and the time is 2 hours; the number average molecular weight of polyethylene glycol is 800;
[0057] (2) dispersing polyamic acid powder in deionized water, adding an organic base, and stirring until the polyamic acid powder is completely dissolved to obtain a polyamic acid salt solution; the mass ratio of graphene oxide to polyamic acid powder is 1:1; the mass ratio of polyamic acid powder to organic base is 1:0.03; the organic base is triethylamine; the preparation process of polyamic acid powder is: using diamine monomer and dianhydride monomer as raw materials to disperse in N,N-dimethylformamide for polycondensation reaction to prepare polyamic acid solution; pouring the polyamic acid solution into deionized water for precipitation to obtain polyamic acid powder; the dianhydride monomer is a mixture of 4,4'-biphenyl ether dianhydride and biphenyltetracarboxylic acid dianhydride in a molar ratio of 1:1; the diamine monomer is diaminodiphenyl sulfone;
[0058] (3) adding the aminated boron nitride nanosheets into the polyamic acid salt solution and dispersing by ultrasonication to obtain a polyamic acid salt mixed solution; the mass ratio of the polyamic acid powder to the aminated boron nitride nanosheets is 1:0.3;
[0059] (4) adding the polyamic acid salt mixed solution dropwise to the graphene hydrogel solution while stirring, and allowing the solution to stand after the addition is complete to obtain a polyamic acid / boron nitride / graphene mixed hydrogel;
[0060] (5) The polyamic acid / boron nitride / graphene mixed hydrogel is freeze-dried, thermally imidized, and crushed to obtain a high thermal conductive gel powder.
[0061] A 3D printing polyurethane material comprises the following components in parts by weight:
[0062] 100 parts of thermoplastic polyurethane elastomer; 15 parts of high thermal conductivity gel powder; 4 parts of zinc stearate.
[0063] Example 4
[0064] A method for preparing a high thermal conductive gel powder comprises the following steps:
[0065] (1) Graphene oxide, a reducing agent and polyethylene glycol are dispersed in deionized water to obtain a graphene oxide mixed solution, which is then sealed and placed in an oven for heating to obtain a graphene hydrogel solution; the graphene oxide concentration in the graphene oxide mixed solution is 1 mg / mL; the reducing agent is ascorbic acid, and the mass ratio of graphene oxide to the reducing agent is 1:0.5; the mass ratio of graphene oxide to polyethylene glycol is 1:0.03; the heating reaction temperature is 80°C, and the time is 2 hours; the number average molecular weight of polyethylene glycol is 800;
[0066] (2) Dispersing polyamic acid powder in deionized water, adding an organic base, and stirring until the polyamic acid powder is completely dissolved to obtain a polyamic acid salt solution; the mass ratio of graphene oxide to polyamic acid powder is 1:0.5; the mass ratio of polyamic acid powder to organic base is 1:0.18; the organic base is tripropylamine; the preparation process of polyamic acid powder is: using diamine monomer and dianhydride monomer as raw materials to disperse in N,N-dimethylformamide for polycondensation reaction to prepare polyamic acid solution; pouring the polyamic acid solution into deionized water for precipitation to obtain polyamic acid powder; the dianhydride monomer is 3,3',4,4'-benzophenonetetracarboxylic dianhydride; the diamine monomer is a mixture of m-phenylenediamine and 4,4'-diaminodiphenylmethane in a molar ratio of 1:1;
[0067] (3) adding the aminated boron nitride nanosheets into the polyamic acid salt solution and dispersing by ultrasonication to obtain a polyamic acid salt mixed solution; the mass ratio of the polyamic acid powder to the aminated boron nitride nanosheets is 1:0.6;
[0068] (4) adding the polyamic acid salt mixed solution dropwise to the graphene hydrogel solution while stirring, and allowing the solution to stand after the addition is complete to obtain a polyamic acid / boron nitride / graphene mixed hydrogel;
[0069] (5) The polyamic acid / boron nitride / graphene mixed hydrogel is freeze-dried, thermally imidized, and crushed to obtain a high thermal conductive gel powder.
[0070] A 3D printing polyurethane material comprises the following components in parts by weight:
[0071] 100 parts of thermoplastic polyurethane elastomer; 15 parts of high thermal conductivity gel powder; 2 parts of zinc stearate.
[0072] Example 5
[0073] A method for preparing a high thermal conductive gel powder comprises the following steps:
[0074] (1) Graphene oxide, a reducing agent and polyethylene glycol are dispersed in deionized water to obtain a graphene oxide mixed solution, which is then sealed and placed in an oven for heating to obtain a graphene hydrogel solution; the graphene oxide concentration in the graphene oxide mixed solution is 1 mg / mL; the reducing agent is ascorbic acid, and the mass ratio of graphene oxide to the reducing agent is 1:0.3; the mass ratio of graphene oxide to polyethylene glycol is 1:0.06; the heating reaction temperature is 70°C, and the time is 2 hours; the number average molecular weight of polyethylene glycol is 800;
[0075] (2) Dispersing polyamic acid powder in deionized water, adding an organic base, and stirring until the polyamic acid powder is completely dissolved to obtain a polyamic acid salt solution; the mass ratio of graphene oxide to polyamic acid powder is 1:0.4; the mass ratio of polyamic acid powder to organic base is 1:0.1; the organic base is triethylamine; the preparation process of polyamic acid powder is: using diamine monomer and dianhydride monomer as raw materials to disperse in N,N-dimethylformamide for polycondensation reaction to prepare polyamic acid solution; pouring the polyamic acid solution into deionized water for precipitation to obtain polyamic acid powder; the dianhydride monomer is a mixture of biphenyltetracarboxylic dianhydride and bisphenol A type diether dianhydride in a molar ratio of 1:1; the diamine monomer is 4,4'-diaminodiphenyl ether;
[0076] (3) adding the aminated boron nitride nanosheets into the polyamic acid salt solution and dispersing by ultrasonication to obtain a polyamic acid salt mixed solution; the mass ratio of the polyamic acid powder to the aminated boron nitride nanosheets is 1:0.5;
[0077] (4) adding the polyamic acid salt mixed solution dropwise to the graphene hydrogel solution while stirring, and allowing the solution to stand after the addition is complete to obtain a polyamic acid / boron nitride / graphene mixed hydrogel;
[0078] (5) The polyamic acid / boron nitride / graphene mixed hydrogel is freeze-dried, thermally imidized, and crushed to obtain a high thermal conductive gel powder.
[0079] A 3D printing polyurethane material comprises the following components in parts by weight:
[0080] 100 parts of thermoplastic polyurethane elastomer; 15 parts of high thermal conductivity gel powder; 5 parts of zinc stearate.
[0081] Example 6
[0082] A method for preparing a high thermal conductive gel powder comprises the following steps:
[0083] (1) Graphene oxide, a reducing agent and polyethylene glycol are dispersed in deionized water to obtain a graphene oxide mixed solution, which is then sealed and placed in an oven for heating to obtain a graphene hydrogel solution; the graphene oxide concentration in the graphene oxide mixed solution is 1 mg / mL; the reducing agent is ascorbic acid, and the mass ratio of graphene oxide to the reducing agent is 1:0.3; the mass ratio of graphene oxide to polyethylene glycol is 1:0.06; the heating reaction temperature is 70°C, and the time is 2 hours; the number average molecular weight of polyethylene glycol is 800;
[0084] (2) Dispersing polyamic acid powder in deionized water, adding an organic base, and stirring until the polyamic acid powder is completely dissolved to obtain a polyamic acid salt solution; the mass ratio of graphene oxide to polyamic acid powder is 1:0.4; the mass ratio of polyamic acid powder to organic base is 1:0.1; the organic base is triethylamine; the preparation process of polyamic acid powder is: using diamine monomer and dianhydride monomer as raw materials to disperse in N,N-dimethylformamide for polycondensation reaction to prepare polyamic acid solution; pouring the polyamic acid solution into deionized water for precipitation to obtain polyamic acid powder; the dianhydride monomer is a mixture of biphenyltetracarboxylic dianhydride and bisphenol A type diether dianhydride in a molar ratio of 1:1; the diamine monomer is 4,4'-diaminodiphenyl ether;
[0085] (3) adding the aminated boron nitride nanosheets into the polyamic acid salt solution and dispersing by ultrasonication to obtain a polyamic acid salt mixed solution; the mass ratio of the polyamic acid powder to the aminated boron nitride nanosheets is 1:0.1;
[0086] (4) adding the polyamic acid salt mixed solution dropwise to the graphene hydrogel solution while stirring, and allowing the solution to stand after the addition is complete to obtain a polyamic acid / boron nitride / graphene mixed hydrogel;
[0087] (5) The polyamic acid / boron nitride / graphene mixed hydrogel is freeze-dried, thermally imidized, and crushed to obtain a high thermal conductive gel powder.
[0088] A 3D printing polyurethane material comprises the following components in parts by weight:
[0089] 100 parts of thermoplastic polyurethane elastomer; 15 parts of high thermal conductivity gel powder; 5 parts of zinc stearate.
[0090] Example 7
[0091] A method for preparing a high thermal conductive gel powder comprises the following steps:
[0092] (1) Graphene oxide, a reducing agent and polyethylene glycol are dispersed in deionized water to obtain a graphene oxide mixed solution, which is then sealed and placed in an oven for heating to obtain a graphene hydrogel solution; the graphene oxide concentration in the graphene oxide mixed solution is 1 mg / mL; the reducing agent is ascorbic acid, and the mass ratio of graphene oxide to the reducing agent is 1:0.3; the mass ratio of graphene oxide to polyethylene glycol is 1:0.06; the heating reaction temperature is 70°C, and the time is 2 hours; the number average molecular weight of polyethylene glycol is 800;
[0093] (2) Dispersing polyamic acid powder in deionized water, adding an organic base, and stirring until the polyamic acid powder is completely dissolved to obtain a polyamic acid salt solution; the mass ratio of graphene oxide to polyamic acid powder is 1:0.4; the mass ratio of polyamic acid powder to organic base is 1:0.1; the organic base is triethylamine; the preparation process of polyamic acid powder is: using diamine monomer and dianhydride monomer as raw materials to disperse in N,N-dimethylformamide for polycondensation reaction to prepare polyamic acid solution; pouring the polyamic acid solution into deionized water for precipitation to obtain polyamic acid powder; the dianhydride monomer is a mixture of biphenyltetracarboxylic dianhydride and bisphenol A type diether dianhydride in a molar ratio of 1:1; the diamine monomer is 4,4'-diaminodiphenyl ether;
[0094] (3) adding the aminated boron nitride nanosheets into the polyamic acid salt solution and dispersing by ultrasonication to obtain a polyamic acid salt mixed solution; the mass ratio of the polyamic acid powder to the aminated boron nitride nanosheets is 1:1;
[0095] (4) adding the polyamic acid salt mixed solution dropwise to the graphene hydrogel solution while stirring, and allowing the solution to stand after the addition is complete to obtain a polyamic acid / boron nitride / graphene mixed hydrogel;
[0096] (5) The polyamic acid / boron nitride / graphene mixed hydrogel is freeze-dried, thermally imidized, and crushed to obtain a high thermal conductive gel powder.
[0097] A 3D printing polyurethane material comprises the following components in parts by weight:
[0098] 100 parts of thermoplastic polyurethane elastomer; 15 parts of high thermal conductivity gel powder; 5 parts of zinc stearate.
[0099] Comparative Example 1
[0100] The preparation process is substantially the same as that of Example 5, except that the mass ratio of the polyamic acid powder to the organic base is 1:0.5.
[0101] The 3D printed polyurethane materials in Examples 1-7 and Comparative Example 1 were printed into strips, and the tensile properties of the strips were tested with reference to GB / T528-2009 Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber, and the thermal conductivity of the strips was tested with reference to ASTM E1461.
[0102]
[0103] Figure 1 This is a scanning electron microscope image of the high thermal conductivity gel powder prepared in Example 5. As can be seen from the figure, the present invention successfully prepared a polyimide / boron nitride / graphene composite thermal conductive gel powder, and an obvious lamellar structure can be seen from the figure. The gel pores are large, which facilitates the full infiltration of the thermoplastic polyurethane elastomer during the 3D printing process and improves the mechanical properties of the composite material. Figure 2 The scanning electron microscope image of the high thermal conductivity gel powder prepared in Comparative Example 1. As can be seen from the figure, the excessive amount of organic base added in Comparative Example 1 affects the reaction between the polyamic acid salt solution and the amino boron nitride nanosheets, resulting in uneven dispersion of the amino boron nitride nanosheets, a smaller pore size of the prepared gel, and a reduced pore structure, which is not conducive to the infiltration of the thermoplastic polyurethane elastomer and affects the formation of a three-dimensional thermal conductive network channel. It can also be seen from Table 1 that the present invention uses polyamic acid salt as a medium to connect graphene gel and amino boron nitride nanosheets, so that graphene and amino boron nitride nanosheets can be mixed at the micron level. This micron-level dispersion can improve the dispersion of fillers in the thermoplastic polyurethane resin matrix, thereby forming more thermal conductive pathways. The three-dimensional graphene gel is used as a reinforcing skeleton and thermal conductive filler, and the two-dimensional boron nitride nanosheets are used as thermal conductive reinforcing fillers. When used in combination with the three-dimensional graphene gel, a synergistic effect can be achieved to form a three-dimensional network thermal conductive pathway, thereby improving the thermal conductivity of the thermoplastic polyurethane composite material at a very small addition amount.
[0104] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, a person skilled in the art should understand that the specific implementation modes of the present invention can still be modified or replaced by equivalents, and any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be included in the scope of the claims.
Claims
1. A method for preparing a high thermal conductive gel powder, characterized in that: The following steps are involved: (1) dispersing graphene oxide, a reducing agent, and polyethylene glycol in deionized water to obtain a graphene oxide mixed solution, sealing the mixed solution, and placing the mixed solution in an oven for heating to obtain a graphene hydrogel solution; (2) dispersing polyamic acid powder in deionized water, adding an organic base, and stirring until the polyamic acid powder is completely dissolved to obtain a polyamic acid salt solution; the mass ratio of graphene oxide to polyamic acid powder is 1:(0.3-1); the mass ratio of polyamic acid powder to organic base is 1:(0.01-0.2); (3) adding the aminated boron nitride nanosheets into the polyamic acid salt solution and dispersing by ultrasonication to obtain a polyamic acid salt mixed solution; the mass ratio of the polyamic acid powder to the aminated boron nitride nanosheets is 1:(0.1-1); (4) adding the polyamic acid salt mixed solution dropwise to the graphene hydrogel solution while stirring, and allowing the solution to stand after the addition is complete to obtain a polyamic acid / boron nitride / graphene mixed hydrogel; (5) The polyamic acid / boron nitride / graphene mixed hydrogel is freeze-dried, thermally imidized, and crushed to obtain a high thermal conductive gel powder.
2. The method for preparing a high thermal conductive gel powder according to claim 1, characterized in that: Step (1) The concentration of graphene oxide in the graphene oxide mixed solution is 0.5-2 mg / mL; the reducing agent is ascorbic acid, and the mass ratio of graphene oxide to the reducing agent is 1:(0.1-0.5); the mass ratio of graphene oxide to polyethylene glycol is 1:(0.01-0.1); the heating reaction temperature is 60-90°C and the time is 1-4h.
3. The method for preparing a high thermal conductive gel powder according to claim 1, characterized in that: The organic base in step (2) is at least one of triethylamine, tripropylamine and triethanolamine.
4. The method for preparing a high thermal conductive gel powder according to claim 1, characterized in that: The preparation process of the amino boron nitride nanosheets in step (3) is as follows: the hexagonal boron nitride powder, urea and deionized water are uniformly mixed and then put into a ball mill, and under the protection of inert gas, the amino boron nitride nanosheets are obtained by high-speed ball milling, washing and drying.
5. The method for preparing a high thermal conductive gel powder according to claim 4, characterized in that: The mass ratio of hexagonal boron nitride powder to urea is 1:(15-30).
6. The method for preparing a high thermal conductive gel powder according to claim 4, characterized in that: The ball mill speed is 400-500 rpm, the ball milling time is 5-10 h, and the inert gas is nitrogen.
7. The method for preparing a high thermal conductive gel powder according to claim 4, characterized in that: The washing step is to use deionized water for 3-5 times.
8. A high thermal conductivity gel powder, characterized in that: The high thermal conductive gel powder is prepared by the preparation method of any one of claims 1 to 7.
9. An application of the high thermal conductivity gel powder as claimed in claim 8, characterized in that: Use high thermal conductivity gel powder in the field of 3D printing polyurethane materials.
10. A 3D printing polyurethane material, characterized in that: Contains the following components in parts by weight: 100 parts of thermoplastic polyurethane elastomer; 5-25 parts of high thermal conductivity gel powder; 1-5 parts of flow modifier; the high thermal conductivity gel powder is the high thermal conductivity gel powder according to claim 8.
Citation Information
Patent Citations
Method for preparing polyimide-graphene composite aerogel through in-situ polymerization
CN106750290A
Structured carbon aerogel based on 3D printing and preparation method thereof
CN110357067A
Impedance gradient type graphene-based polyimide composite foam wave-absorbing material
CN112094426A
Heat conduction composite material and preparation method thereof
CN112409791A
Functionalized boron nitride nanosheet / MXene / polybenzimidazole high-thermal-conductivity composite film and preparation method thereof
CN112552681A
